Role of Gender in Consumers’ Response to Fear Appeal Advertisements - Ajit, S.; Joseph Paul Raj, V. (Indian Journal of Marketing, 2012)
In today’s world, the dynamic nature of consumers, their needs and wants are reflected in their response to marketing stimuli usually done by advertising. There is a marked difference in the influence of males and females in decision making for buying goods and services. It is of utmost importance for the marketers to understand each and every customer’s needs to achieve effectiveness of marketing activities. It is logical that each individual may have unique responses to different types of advertisements according to their characteristics, and they may react most positively when exposed to advertisements that match their personality. Fear appeal ads, as a tactic of persuasion, influence that attitude and behaviour of customers. The purpose of this study is to investigate whether gender influences the responses to fear appeal advertisements. The results of the study show that fear appeal advertisements are effective in changing the perception of respondents towards bad oral care. It was found that there was a significant difference in the perception of male and female respondents towards health and social consequences of bad oral care before and after watching the advertisements.